Evaluation of the Inhibitory Activities against α-amylase and α-glucosidase of Selected Medicinal Plants Harvested in Ninh Binh Province - Duc Loi, Vu; Phuong Dung, Nguyen; Xuan Tung, Nguyen; Hong Duong, Le (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
Abstract: Plants are potential sources containing secondary metabolites that can inhibit α-amylase and α-glucosidase enzymes, two key target enzymes in the treatment of diabetes. Therefore, this study was conducted to evaluate the ability of eight medicinal plants collected in Ninh Binh province to inhibit the α-amylase and α-glucosidase enzymes. The investigated medicinal plants were soaked and then ultrasonically extracted with methanol 70%. The enzymatic inhibitory potential of the plant extracts was evaluated by measuring the optical absorbance of the solution after the reaction had occurred. The obtained results indicated that the stem and leaf extract of Commelina diffusa showed good inhibitory effects in both assays, with IC 50 values of 64.65 µg/mL for α-amylase enzyme and 68.39 µg/mL for α-glucosidase enzyme. These effects were all better than those of acarbose (IC 50 values were 72.42 µg/mL and 98.17 µg/mL, respectively). The results of this study showed that the 70% methanolic extract of Commelina diffusa has potential in supporting the prevention and treatment of diabetes. Keywords: Diabetes, α-amylase, α-glucosidase, acarbose, medicinal plants, Commelina diffusa .